Eksistensi Museum Pusaka Nias Dalam Pariwisata Kepulauan Nias Tahun 1995-2020 - Nofe Firman Zai; Erniwati Erniwati (Jurnal Kronologi, 2022)
This article discusses the development of the Nias Heritage Museum and its existence as well as its role in Nias island tourism in 1995-2020. This research is a historical research through the stages of heuristics, verification/criticism, interpretation, and historiography. Sources were obtained through library research in the form of books and journals, document studies in the form of photographs of the Nias Heritage Museum collection, data on the number of visitors and data on the acquisition status of the Nias Heritage Museum collections, and the Decree of the Permit to Build Building by the Regent of Nias, as well as field studies by interview. and observation. This article shows that the Nias Heritage Museum since 1995 has collected various cultural products of the Nias people, such as artifacts, miniatures of the life of the nobles of the Nias tribe, megalith stones, statues, and jewelry of the nobles of the Nias tribe which later became an attraction for tourists. The function of the Nias Heritage Museum has been increasingly visible since its inauguration in 2008 as a medium of information, education, documentation, and a means of conserving the cultural heritage of the Nias people, either in the form of tangible heritage or intangible heritage. Until now the Nias Heritage Museum still exists in conserving cultural heritage and educating the public through tourism activities based on cultural history.